Study on physico-chemical properties of aonla (Emblica officinalis Gaertn.) cultivars during fruit growth and development (Indian Journal of Arid Horticulture, 2025)
To evaluate the aonla cultivars in Chhattisgarh the physico-chemical characters of eight aonla cultivars viz. Banarasi, Chakaiya, Francis, Kanchan, Krishna, NA-6, NA-7 and NA-10 were studied. Significant variation in average weight, volume, length, diameter and stone weight of different cultivars were found coupled with a similar variation in their contents of TSS, acidity, ascorbic acid and total sugars. Among the physical characters at maturity the maximum dimensions of fruit weight, fruit volume, fruit diameter, fruit length and stone weight respectively were possessed by the cvs. Banarasi (57.74 g), Krishna (57.97 ml), NA-7 (4.38 cm), Banarasi (4.76 cm) and Krishna (5.03 g). Similarly, among the chemical characters at maturity the maximum chemical content of TSS, acidity, ascorbic acid and total sugars respectively were possessed by the cvs. Banarasi (15.71%), Banarasi (2.32%), Banarasi (882.11 mg/100g of pulp) and Krishna (8.23%). Thus, from the overall physical characteristics point of view the cv. Banarasi may be declared to be of best fruit size (fruit weight = 57.74 g, fruit volume = 56.68 ml, fruit diameter = 4.10 cm, fruit length = 4.76 cm) followed by Krishna, Kanchan, Chakaiya and Francis, with the fruit of most inferior size to be the cv. NA-6. Similarly, from the chemical characteristics point of view, the best chemical composition at maturity may be attributed to Banarasi (TSS= 15.71%, acidity = 2.32%, total sugars = 8.09%, ascorbic acid = 882.11 mg/100g of pulp) followed by the cvs. Chakaiya and Francis. However, no single cultivar stands out to be of most inferior chemical quality.
Keywords: Aonla; growth; development; physico-chemical characteristic.